Internationalization of Russian Education: an Analysis of Expert Assessments - Nina V. Shevchuk (Евразийская интеграция: экономика, право, политика, 2019)
The article is devoted to the problems of Russian educational services promoting to international markets. The author carried out the analysis of the efforts made at the government level and a wide range of expert assessments on the studied issues. The author proposeda number of recommendations for developing a new strategy for promoting Russian educational services and to increase the number of Asian, Eastern European and Western European students in Russian universities.